CP-099 Fampridine, a new approach in the treatment of multiple sclerosis: efficacy in improving walking and quality of life. (24th March 2015) - Barbadillo, S; Benito, V; Aicua, I; Calvo, S; Hermida, C; Herrera, N; Fernandez, M; Cabia, L
Abstract : Background: Multiple Sclerosis (MS) is a neurological disease in which myelin is destroyed, impairing nerve impulse conduction. Fampridine is the first drug authorised for improving walking. It is a potassium channel blocker that improves electrical transmission for muscle stimulation. Purpose: To describe changes in quality of life of patients receiving fampridine regarding health perception (subjective change) and improved walking (objective change). Material and methods: Prospective study during the first two weeks of patient treatment. Patients received fampridine 10 milligrams every 12 h plus their usual MS drugs. Health perception was measured by MS Quality Of Life-54 questionnaires and point-in-time assays of physical and mental health before and after taking fampridine. Changes in walking were measured by the Timed 25-Foot Walk (T25FW) test (time to walk 7.5 metres). Sample population was characterised by age, type of MS, and Expanded Disability Scale System (EDSS) point-in-time assays (disability due to MS from 1 to 10, 10 being death). Results before and after treatment were analysed with Student's t-test. Statistically significant relationships between variables were evaluated by applying appropriate tests. Results: 39 patients, mean age 49, standard deviation (σ) 12.6. 15.4% had Relapsing-Remitting MS, 69.2% Secondary Progressive MS and 15.4% Primary Progressive MS. Mean EDSS score 5.5, σ 1.15. Physical health improved 9.05 points, confidence interval CI (5.57–12.52), p < 0.05. Mental health improved 6.62 points CI (3.58–9.68) p < 0.05. TW25F was reduced by 9.04 s CI (–11.93, –6.14), p < 0.05. Improvement was independent of MS type and EDSS punctuation, p < 0.05. Physical and mental improvement were directly related. Conclusion: The rapid effect of fampridine was obvious. Improvement in physical health (both subjective and objective measures) was observed. This might be because the mechanism of action directly targets the motor system. The relationship between physical and mental improvement is coherent, because personal autonomy raises self-esteem. Evaluation in larger samples and over a longer period is needed in order to substantiate a maintained benefit. References and/or Acknowledgements: No conflict of interest.